The Role Of Religious Morals On Students' Academic Cheating Behavior During Online Learning During The Covic-19 Period - Ariani, Meiliyah; Ismi Islami, Dian (International Journal of Educational Research & Social Sciences, 2022)
Cheating behavior is a dishonest act carried out by someone in order to get a satisfactory end result. Academic cheating is still often done by students, to get high grades. The emergence of a feeling of worry or feeling threatened that is felt because of the inability or less than optimal of a student in completing his college assignments triggers students to commit academic fraud due to various demands from the environment that expect high results and grades. This study aims to determine the effect of academic integrity factors and religious moral factors on student academic cheating during online learning during the Covid-19 period at Prof. University. Dr. Moestopo (Religious) Academic Year 2021-2022 even.The sample method used is purposive sampling. The number of students who were sampled in this study were 350 students of Prof. University. Dr. Moestopo (Religious), Even Semester. The data used is primary data in the form of questionnaires distributed to respondents using google form facilities. This analysis method uses descriptive statistical tests, data quality tests, classical assumption tests, data analysis tests and model suitability tests using the SPSS program.The results showed that religious moral factors and academic integrity had a significant effect on students' academic cheating behavior. Partially, this study shows that religious moral factors have a negative and significant effect, while academic integrity factors have a positive and significant effect on academic cheating behavior in the online learning system.